Simulations and Experiments on the Vibrational Characteristics of Cylindrical Shell Resonator Actuated by Piezoelectric Electrodes with Different Thicknesses - Yiming Luo (Shock and Vibration, 2017)
The resonator is the key element of the Coriolis Vibratory Gyroscope (CVG). The vibrational characteristics of the resonator, including the resonant frequency, vibrational amplitude, and Q factor, have a great influence on CVG’s performance. Among them, the vibrational amplitude mainly affects the scale factor and the signal-to-noise ratio, and the Q factor directly determines the precision and drift characteristics of the gyroscope. In this paper, a finite element model of a cylindrical shell resonator actuated by piezoelectric electrodes with different thicknesses is built to investigate the vibrational characteristics. The simulation results indicate that the resonant frequency barely changes with the electrode thickness, whereas the vibrational amplitude is inversely proportional to the electrode thickness under the same driving voltage. Experiments were performed with four resonators and piezoelectric electrodes of four sizes, and results were consistent with simulations. The resonant frequencies of four resonators changed within 0.36% after attaching the piezoelectric electrodes. Meanwhile, with the same driving voltage, it was shown that the vibrational amplitude decreased with the increase of electrode thickness. Moreover, thinner electrodes resulted in better Q factor and therefore better performance. This study may provide useful reference on electrode design of the CVGs.